2019
DOI: 10.1002/smll.201904613
|View full text |Cite
|
Sign up to set email alerts
|

In‐Plane Potential Gradient Induces Low Frictional Energy Dissipation during the Stick‐Slip Sliding on the Surfaces of 2D Materials

Abstract: Understanding the nanoscale friction properties of 2D materials and further manipulating their friction behaviors is of great significance for the development of various micro/nanodevices. Recent studies, taking advantage of the close relationship between friction and surface charges, use an external out‐of‐plane electric field to control the interfacial friction. Nevertheless, friction increases with the application of the out‐of‐plane electric field in most cases. Here, an in‐plane potential gradient is appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
(62 reference statements)
0
15
0
1
Order By: Relevance
“…Many effective methods, such as designing interfacial or contacting structures, decreasing surface roughness and mechanical loading, and adding solid or liquid lubricant additives, have been developed to control and reduce friction and wear. Previous studies have shown that applying external electric fields can modify the molecular structure and charge transfer at solid-solid interfaces, thereby decreasing the interfacial friction and resistance [1,2]. Moreover, the distribution or orientation of ions at solid-liquid interfaces can be controlled and changed via electric fields to achieve the desired lubricating effect [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Many effective methods, such as designing interfacial or contacting structures, decreasing surface roughness and mechanical loading, and adding solid or liquid lubricant additives, have been developed to control and reduce friction and wear. Previous studies have shown that applying external electric fields can modify the molecular structure and charge transfer at solid-solid interfaces, thereby decreasing the interfacial friction and resistance [1,2]. Moreover, the distribution or orientation of ions at solid-liquid interfaces can be controlled and changed via electric fields to achieve the desired lubricating effect [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The potential difference between AFM tips with different conductivities and samples was applied to study bias-dependent friction using conductive AFM [38,39]. In addition, Fann et al [40] reported electron dynamics and thermalization in metals and semiconductors on timescales, providing an exciting possibility to control the nanofriction of h-BN by using charges.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies already pointed out that load can be used as an external knob to control the nanoscale friction [11][12][13], although it may induce unwanted permanent changes to the atomic geometry [14][15][16][17]. On the other hand, electrical fields induce charge movements which may alter the frictional properties temporarily, while allowing them to revert to the original structure once the external field is suppressed [18][19][20]. Some theoretical studies have already dealt with the effect of electric fields on the coupling between the electronic and dynamic (i.e., phonon) features in low-dimensional materials [21,22]; interestingly, such coupling has been found to be effective in altering the lateral frictional force in MoS 2 and graphene bilayer systems [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical studies have already dealt with the effect of electric fields on the coupling between the electronic and dynamic (i.e., phonon) features in low-dimensional materials [21,22]; interestingly, such coupling has been found to be effective in altering the lateral frictional force in MoS 2 and graphene bilayer systems [23,24]. Recent experimental studies showed how to manipulate free-standing atomic layers by in-plane potential gradients with an atomic force microscopy tip [6,25], while the friction between the tip and the layer decreases with the field [20].…”
Section: Introductionmentioning
confidence: 99%